A case report of successful splenic artery embolization for atraumatic splenic rupture secondary to Epstein Barr virus infection in a haemodynamically unstable patient - Naradha Lokuhetty, MBBS (Hons); Moira Tereapii Philip, BBMed MD; Jessica Anne Paynter, MBBS (Hons), BMedSc; Andrew Robert Owen, BSc MBBS MRCP FRCR FRANZCR (Radiology Case Reports, 2024)
Splenic rupture in haemodynamically unstable patients has traditionally been managed with splenectomy. This case report discusses the successful management of atraumatic splenic rupture, a rare but life-threatening complication of Epstein-Barr virus (EBV) infection, in a hemodynamically unstable patient. The patient, diagnosed with infectious mononucleosis (IM) secondary to EBV, presented with severe abdominal pain and a syncopal episode. Imaging revealed an American Association for the Surgery of Trauma (AAST) grade III splenic injury, which was subsequently upgraded to a grade IV injury on repeat imaging. The patient's condition deteriorated even with initial resuscitation, leading to splenic angioembolization. The procedure was successful and the patient was discharged after 5 days. This case highlights the efficacy of splenic artery embolization (SAE) in haemodynamically unstable patients with atraumatic splenic rupture, particularly in centers with interventional radiology resources, offering an alternative to splenectomy and its associated complications.